Fault-Tolerant Control Strategy for Neutral-Point-Clamped Three-Level Inverter - Yanxia Shen; Beibei Miao; Dinghui Wu; Kader Ali Ibrahim (Journal of Control Science and Engineering, 2018)
A fault-tolerant control technique is discussed for the Neutral-Point-Clamped (NPC) three-level inverter, which ensures that the NPC inverter operates normally even under device failures. A two-level leg is added to the NPC inverter; when the device open circuit fault occurs, the load of this faulty phase is connected to the neutral point of this two-level leg through the bidirectional thyristors. An improved Space Vector Pulse Width Modulation (SVPWM) strategy called “addition and subtraction substitution SVPWM” is proposed to effectively suppress fluctuation in capacitor neutral-point voltages by readjusting the sequence and action time of voltage vectors. The fault-tolerant topology in this paper has the advantages of fewer switching devices and lower circuit costs. Experimental results show that the proposed fault-tolerant system can operate in balance of capacitor neutral-point voltages at full output power and the reliability of the inverter is greatly enhanced.